Dauru Nasyatu Al-Muhadatsah As-sobahiyah fi Tarqiyah Kafa’atu At-Tholibat fi Maharati Al-Kalam Al-Fasli Al-awal Al-‘aly bima’had Al-Adabi Mampuang Kalimantan - Anugerah, Rizka; Nurusyifa (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to determine the role of Muhadatsah in improving the learning outcomes of Maharah Kalam students at the Al Adabiy Islamic Boarding School, because in this boarding school, muhadatsah activities or daily conversations using Arabic are implemented so that researchers want to know the contribution of this activity to the development of speaking skills and want to know the problems to improve speaking skills. Researchers see that the cause of the lack of students' abilities in Arabic speaking skills is the lack of mastery of Arabic vocabulary, the lack of practice speaking Arabic which has an effect on improving speaking skills. In this study, researchers used a qualitative approach with a descriptive qualitative type. The method of data collection used observation, interviews and documentation. The data analysis used data exposure, data analysis and data reduction which aimed to determine the role of muhadatsah in improving speaking skills so that researchers could take the values ??in this study. The results showed that 1) the role of muhadatsah in improving speaking skills is that students are fluent in speaking Arabic, fluent in pronouncing hijaiyah letters, enthusiastic in learning Arabic, activating the language environment, increasing mastery of Arabic vocabulary, and helping to train themselves in speaking Arabic. 2) The problems found in learning muhadatsah to improve speaking skills are limited vocabulary mastery, low motivation, fear of making mistakes, weakness in nahwu and sharaf knowledge, and the solution to these problems is that students must memorize a lot of Arabic vocabulary, eliminate the fear of making mistakes, learn nahwu and sharaf, get used to hearing Arabic, and motivate themselves to practice speaking Arabic.